Private Providers and the Expansion of Collaborative Higher Education in the UK: unintended effects of deregulation? - Mariampillai, John (Advances in Social Sciences Research Journal, 2019)
The higher education sector in the UK has witnessed major changes in recent times, including the expansion of private HE provision. Education has a special place in a society, and it plays a major role; it creates productive workforce, offers social mobility and contributes to the economic growth and prosperity of a nation. Therefore, the decision to open-up the higher education market to private providers has met with public debate and scrutiny. This article examines the existence, growth and the approaches adopted by the successive governments since 2010 to organise private provision in the UK higher education.